The Concept of Malakah Ibn Khaldun in the Context of Teaching that Applies High Order Thinking Skills (HOTS) - Mohd Syaubari Bin Othman; Hasrul Hoshan; Abu Bakat Yusof; Zaini Abdullah; Abd Talib Mohamed (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The high order thinking skills (HOTS) is a transformation in the education system in Malaysia this century in line with the implementation of the Malaysia Education Blueprint 2013-2025. The practice of implementing HOTS has outperformed the entire subject content concept by focusing on several HOTS theories in particular the Bloom and Taxonomy Marzano taxonomy. However, for the Islamic Education subjects based on the Quran and As-Sunnah, the implementation of this HOTS element needs to be translated through the basis of the Islamic Education Philosophy that puts the perfectional of the intellectual education as the main thrust in driving this thinking culture. The emergence of figures such as Ibn Khaldun, which speaks thoroughly of the mind-based concept of Malakah, has sparked diversity in the perspective of the understanding of HOTS understanding. For this reason, this study uses the analysis process by analyzing the literature by examining the contents of a synonymity or summarized in the meaning of the poor concept of Ibn Khladun in the context of the teaching of Islamic education subjects. The results of this study resulted in four basic concepts in the application of HOTS through the use of Malakah combined with the use of aql tamyizi, aql tajribi, aqal nazori and insaniyah fact. In general, the implementation of Islamic Education PdP which implements HOTS should focus on the process and philosophy of teaching that Ibn Khaldun has established to ensure that students' understanding, appreciation and practice assesses the requirements set out on the basis of the Islamic Education Philosophy. The conclusions of the findings of this study contribute the implementation of HOTS in Islamic Education Pedagogy should focus on the teaching process and philosophy established by Ibn Khaldun, ensuring that students' understanding, appreciation, and practice align with the requirements based on the Islamic Education Philosophy.